ENHANCING STUDENTS’MATH LEARNING OUTCOMES ON DETERMINING MULTIPLICATION OPERATION MATERIAL THROUGH NUMBERED HEAD TOGETHER (NHT) MODEL - Yenita Yenita (Ta'dib, 2017)
This study aims at describing the use of multiplication operations through number head together strategy in improving mathematics learning outcomes.  This is a classroom action research using qualitative and quantitative data. The research procedures are: planning stage, implementation stage, observation stage, and reflection stage. The data were obtained through writing test and observation sheet. The subjects of the study were the fourth graders of SD 04 Koto Gadang Kec. Padang Ganting, Tanah Datar regency, the academic year 2015/2016. The results shows that in Cycle I, the determining multiplication operations through cooperative learning type Numbered Heads Together (NHT) can improve 71% of students’ math learning outcome. Besides, based on the observation result, it is found that the teacher activity in teaching cycle I was 74% accomplished, and the student activity 77% of the average meeting I and II. Moreover, in Cycle II, students' activities increased to be 89%, and the students’ to be 92% of average meeting I and II. It is summarized that cooperative learning type Numbered Heads Together (NHT) can improve the students’ mathematics learning outcomes on the determining multiplication operation materials in Class IV SDN 04 Koto Gadang Padang Ganting Subdistrict Tanah Datar